(untitled) (Tanzania Medical Journal, 2021)
Introduction Obstructive jaundice is defined as a condition occurring due to a block in the pathway between the site of conjugation of bile in liver cells and the entry of bile into the duodenum through the ampulla. The block may be intrahepatic or extrahepatic in the bile duct. Majority of the patients with portal biliopathy are asymptomatic and only about 20% presents with symptoms hence management is limited to this group and is dictated by the clinical manifestations and complications. Case presentation We are reporting a case of female patient aged 66 years who had features of obstructive jaundice. Abdominal CT-scan revealed obstructive biliopathy due to compression of the extrahepatic common bile duct by dilated periportal collaterals. She underwent bypass cholecystojejunostomy with Braun’s anastomosis surgery with no morbidities and her jaundice resolved clinically. Conclusion Jaundice due to extra-hepatic biliary obstruction may arise as a result of diverse clinical conditions ranging from those commonly encountered during routine clinical practice to the ones which are rarely seen.